2006
DOI: 10.1021/cm0515505
|View full text |Cite
|
Sign up to set email alerts
|

Zn13Sb10:  A Structural and Landau Theoretical Analysis of Its Phase Transitions

Abstract: Composition, crystal structures, polymorphic transformations, and stability of the thermoelectric material known in the literature as "Zn 4 Sb 3 " have been studied on a polycrystalline sample and Bi-flux-grown single crystals using X-ray diffraction techniques, resistance, and Seebeck coefficient measurements at various temperatures ranging from 4 to 773 K. Microprobe analysis yields the composition of the flux-grown crystals to be close to Zn 13 Sb 10 , with minor Bi doping. High-temperature X-ray and Seebec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
87
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 20 publications
17
87
0
Order By: Relevance
“…17, 18 The plateau in resistivity, observed between 230 K and 140 K, may be due to the effect of an impurity scattering process, arising from a phase impurity caused by a ''premature effect'' of the order-disorder phase transition at 250 K. A second phase transition at T Ϸ 234 K has been reported by another group. 19 The slope in resistivity changes below 140 K, decreasing with decrease in temperature in a semimetallic manner. The room temperature resistivity is somewhat higher than that reported in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…17, 18 The plateau in resistivity, observed between 230 K and 140 K, may be due to the effect of an impurity scattering process, arising from a phase impurity caused by a ''premature effect'' of the order-disorder phase transition at 250 K. A second phase transition at T Ϸ 234 K has been reported by another group. 19 The slope in resistivity changes below 140 K, decreasing with decrease in temperature in a semimetallic manner. The room temperature resistivity is somewhat higher than that reported in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] A computationally derived convex hull of formation enthalpies for various binary zinc antimonides predicts ZnSb to have the most negative formation enthalpy. 36 Low-temperature, soft chemistry techniques may provide a reproducible means to observe and isolate many of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Besides increasing the zT, many studies have also been conducted to investigate the thermal stability of this material [11,[21][22][23][24][25][26] . Caillat et al have shown that TE properties of Zn4Sb3 are stable up to 670 K under argon and static vacuum, but unstable in the dynamic vacuum due to the evaporation of Sb at temperatures higher than 543 K resulting in an increased electrical resistivity [11] .…”
Section: Introductionmentioning
confidence: 99%